Pancasila As A Code Of Public Ethics In Modern Democracy - Ahmad Khoirul Ma'sum; Muhammad Abiel Rahman H.; Cecep Soleh Kurniawan (International Journal of Religion and Social Community, 2026)
This study examines Pancasila as a framework for public ethics in modern democracy, highlighting various contemporary challenges such as political polarisation, the decline in public morality, populism, and disruption in the digital sphere. The phenomena of identity politics, the spread of disinformation, and the manipulation of public opinion via social media reveal a gap between the ideal values of Pancasila and democratic practice in Indonesia. To bridge this gap, this study integrates Al-Farabi’s perspective on political ethics as a philosophical foundation for re-actualising the values of Belief in God, Humanity, Unity, Democracy, and Social Justice within the context of contemporary democracy. The research employs a qualitative approach using library research, analysed through a philosophical-interpretative approach to Pancasila texts, the works of Al-Farabi, and the latest literature on public ethics and modern democracy. The research findings indicate that there is a strong convergence between Pancasila and Al-Farabi’s political ethics, particularly in the upholding of public morality, the strengthening of social justice, the development of political integration, and the fostering of rational civic participation oriented towards the common good. These findings confirm that Pancasila remains relevant as the foundation of public ethics in the face of the dynamics of modern democracy, whilst also offering an integrative Pancasila Al-Farabi model as a conceptual framework for strengthening political ethics, democratic governance, and a more civilised public life.